2008
DOI: 10.3382/ps.2007-00476
|View full text |Cite
|
Sign up to set email alerts
|

Detection of T Lymphocytes in Intestine of Broiler Chicks Treated with Lactobacillus spp. and Challenged with Salmonella enterica Serovar Enteritidis

Abstract: The expression of immune response in the form of leukocytic infiltrate by CD3+, CD4+, and CD8+ cells in the epithelium and in the intestinal lamina propria of chicks was studied in the present work by means of immunohistochemical reaction. The chicks were treated with Lactobacillus spp. or cecal microflora (CM) and experimentally challenged or not with Salmonella enterica serovar Enteritidis. The 320 birds utilized were divided into 4 groups containing 80 chicks each and submitted to treatments with Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
2
23
2
3
Order By: Relevance
“…Thus, it is likely that many of probiotic bacteria cause an increase in the density of T cells, especially CD8+ T cells, in the intestinal mucosa of the chicks. Also, such effects of probiotics in the chicks are likely to appear around 7 days after treatment as observed in the current study and by Yurong et al (2005) and Noujaim et al (2008). Although the mechanism by which CD8+ T cells population was enhanced by probiotics in the current study remains unknown, we assume that probiotics might induce some chemokine-or cytokine-like factors affect CD8+ T cells to lead to redistribution of CD8+ T cells from lymphoid tissue to the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Thus, it is likely that many of probiotic bacteria cause an increase in the density of T cells, especially CD8+ T cells, in the intestinal mucosa of the chicks. Also, such effects of probiotics in the chicks are likely to appear around 7 days after treatment as observed in the current study and by Yurong et al (2005) and Noujaim et al (2008). Although the mechanism by which CD8+ T cells population was enhanced by probiotics in the current study remains unknown, we assume that probiotics might induce some chemokine-or cytokine-like factors affect CD8+ T cells to lead to redistribution of CD8+ T cells from lymphoid tissue to the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 61%
“…They showed a higher content of IgA in the intestinal fluid, greater frequencies of IgA-forming cells in the duodenum and T cells in the cecum tonsil at day 7 of treatment. Noujaim et al (2008) also showed a greater quantity of CD3+, CD4+ and CD8+ T cells in the intestine of chicks after 8 to 12 days of treatment with Lactobacillus spp. Thus, it is likely that many of probiotic bacteria cause an increase in the density of T cells, especially CD8+ T cells, in the intestinal mucosa of the chicks.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These results suggest that probiotics may not have a significant effect on AvBD12 expression, but it is possible that the secretion of AvBD12 by the surface epithelium is stimulated by probiotics. Infection by pathogenic agents such as Salmonella and Campylobacter has been shown to increase the expression of chemokines, proinflammatory cytokines (Withanage et al, 2004;Carvajal et al, 2008) and cellular immunoresponse, particularly Th1 response (Berndt et al, 2007;Noujaim et al, 2008). In addition, infection by Salmonella may also upregulate the AvBDs expression in chick cecal tissue (Akbari et al, 2008;Wigley, 2013).…”
Section: Discussionmentioning
confidence: 99%